Extraction Strategies to Recover Bioactive Compounds, Incorporation into Food and Health Benefits - Contreras, María del Mar (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
We are pleased to present this book, which is a reprint of articles from the Special Issue entitled "Extraction Strategies to Recover Bioactive Compounds, Incorporation into Food, and Health Benefits" published online in the open access journal Foods (ISSN 2304-8158) from 2019 to 2020 (available at: https://www.mdpi.com/journal/foods/special_issues/extraction). Firstly, this book gathers studies addressing several strategies applied to obtain bioactive products and extracts, not only from food matrices but also from agri-food byproducts, which can serve as new natural additives, nutraceuticals, and functional ingredients for pharmaceutical, cosmetics, and food industries. In particular, free and bound phenolic compounds are explored in buckwheat, sesame, and olive leafy byproducts. Overall, these studies outline new valorization methods and offer new opportunities for alternative practices in the agro-industrial sector that help to migrate toward a circular bioeconomy model. This book also presents studies that predict bioactive components in fruits through mathematical tools and support the formulation of a novel beverage rich in resveratrol, a phenolic compound whose bioactivity is well recognized.